2012
DOI: 10.1039/c2ra01352e
|View full text |Cite
|
Sign up to set email alerts
|

Direct experimental observation of the aggregation of α-amino acids into 100–200 nm clusters in aqueous solution

Abstract: Spherical supramolecular aggregates of α-amino acids with a typical diameter of 100–200 nm are formed spontaneously after dissolution in water at a concentration of a few mM, i.e. well below the solubility limit. Their presence was shown by nanoparticle tracking analysis (NTA), atomic force microscopy (AFM), and ESI mass spectrometry (ESI-MS). There is a dynamic equilibrium between the aggregates and dissolved individual molecules which allows them to penetrate through dialysis membranes and filters. The same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 15 publications
1
49
2
Order By: Relevance
“…Indeed, the dynamics of organic clusters might generally be slower than those of inorganic compounds, and a qualitative assessment of cluster dynamics by means of AUC cannot provide unambiguous evidence about whether or not the detected clusters are actually phase separated. Also, the much larger amino acid associates reported by Hagmeyer et al 40. and Jawor-Baczynska et al 41.…”
Section: Resultsmentioning
confidence: 91%
“…Indeed, the dynamics of organic clusters might generally be slower than those of inorganic compounds, and a qualitative assessment of cluster dynamics by means of AUC cannot provide unambiguous evidence about whether or not the detected clusters are actually phase separated. Also, the much larger amino acid associates reported by Hagmeyer et al 40. and Jawor-Baczynska et al 41.…”
Section: Resultsmentioning
confidence: 91%
“…Even though we do realize the limitation of such an approach, we believe that it would allow, at least, a direct comparison of our data with other literature on light scattering of solutions of low-molecular-weight compounds. [12,42,43] Typical correlation functions and intensity-weighted size distributions for solutions of d-levoglucosan in water are shown in Table 1S. The DLS data for all concentrations are summarized in Table 3, and the analysis of concentration dependence of size distributions revealed areas of concentration in which similar types of light-scattering "particles" exist.…”
Section: Light Scattering Experimentsmentioning
confidence: 99%
“…It has been shown that intermolecular interaction such as hydrogen bondings between aminoacid molecules can cause formation of aggregates with about 100 to 200 nanometer sizes in water. 34 The aminoacid molecules attached on to the different ZnS:Mn nanocrystals can also attract to each other by hydrogen bonding interaction between aminoacid-aminoacid or aminoacid-water(solvent)-aminoacid moieties. However, since alanine molecules contain an additional free-rotating methyl group from glycine, they can also cause larger van der Waals repulsion between the capping molecules on the different nanocrystals during the aggregation process.…”
mentioning
confidence: 99%